The small phytomolecule resveratrol: A promising role in boosting tumor cell chemosensitivity - Imen Ben Haj Yahia; Olfa Baccouri; Maroua Jalouli; Nadia Boujelbene; Md Ataur Rahman; Abdel Halim Harrath; Ines Zidi (Pensoft Publishers, 2024)
Resveratrol (RES), chemically known as trans-3,5,4'-trihydroxystilbene, is a polyphenolic molecule that occurs naturally and is produced by a variety of plants in response to being stimulated by diverse stimuli. It possesses a wide range of biological activities and provides a multitude of health benefits, including anti-tumor, cardioprotective, anti-inflammatory, and antioxidant characteristics. According to the findings of research on the bioavailability of RES, oral administration results in a high level of absorption. However, research has demonstrated that the administration of RES through gavage or intravenous administration produces more favorable results than the administration of RES through oral administration. As a result, more research has been carried out to address the rapid metabolism of RES. This has been accomplished through the utilization of novel formulation methodologies, metabolic regulation, and the analysis of potential interactions with other dietary variables. Through the process of triggering apoptosis, RES has been proposed as a possible agent for reversing drug resistance and improving the therapeutic potential of chemotherapy. Additionally, RES exhibits promising antiproliferative properties when paired with chemotherapeutic medicines, which enhances the overall function of these treatments. It is vital to do additional research to shed light on the beneficial role that RES plays in the context of cancer therapy, even though there have been few clinical trials that combine RES with anticancer medications.